TRANSITIONAL FEATURES OF ACUTE HERPETIC STOMATITIS IN CHILDREN AND MODERN APPROACHES TO TREATMENT - Berdiyev Ergash Abdullayevich; Boboyorov Sardor Uchqun o’g’li (Scholar Express Journals, 2021)
Herpesviruses are widespread us in the human population. They capable of hitting almost everyone organs and systems, induce neoplastic static processes and development of atherosclerosis, have an adverse effect, and sometimes a fatal effect on the body nism of the fetus and newborns.The article presents characteristic peculiarities of herpetic stomatitis in children. It describes differential diagnostic symptoms. The treatment approaches are given depending on the severity degree of the disease.
Keywords: herpes virus, infection, groprinosin, Oral infection, gingivostomatitis